2015
DOI: 10.1128/jb.00395-15
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Expression of De Novo Pyrimidine Biosynthesis Genes in Corynebacterium glutamicum

Abstract: Expression of pyrimidine de novo biosynthesis is downregulated by an exogenous uracil in many bacteria. In this study, we show that a putative binding motif sequence of PyrR is required for uracil-mediated repression of pyrR-lacZ translational fusion. However, the uracil response was still observed in the strain with the pyrR gene deleted, implying the existence of a uracil response factor other than PyrR which also acts through the PyrR binding loop region. Deletion of rho, encoding the transcription terminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Moreover, studies have shown that uracil is an allosteric regulator and coenzyme in many important biochemical reactions, and participates in a variety of enzyme reactions. 45 Uracil can be phosphorylated by various kinases to produce UMP, UDP, and UTP. UDP and UTP regulate the activity of animal carbamoyl phosphate synthase II, and uracil is also involved in the biosynthesis of polysaccharides and the transport of aldose‐containing sugars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have shown that uracil is an allosteric regulator and coenzyme in many important biochemical reactions, and participates in a variety of enzyme reactions. 45 Uracil can be phosphorylated by various kinases to produce UMP, UDP, and UTP. UDP and UTP regulate the activity of animal carbamoyl phosphate synthase II, and uracil is also involved in the biosynthesis of polysaccharides and the transport of aldose‐containing sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that uracil is an allosteric regulator and coenzyme in many important biochemical reactions, and participates in a variety of enzyme reactions 45 . Uracil can be phosphorylated by various kinases to produce UMP, UDP, and UTP.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of the UMP coregulator, PyrR binds to the 5 ' UTR of the pyrR mRNA transcript and disrupts the anti-terminator stemloop, resulting in decreased downstream gene expression. In contrast, when the UMP concentration is low, PRPP antagonizes UMP termination by binding to the PyrR protein [10][11][12] . The expression of de novo synthesis of pyrimidine genes is regulated by RNA-binding proteins, but it remains unclear whether it is regulated by DNA-binding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrimidine de novo synthesis pathway consists of six enzymatic steps, and the genes encoding these enzymes (carA, carB, pyrB, pyrC, pyrD, pyrE, and pyrF) are widely conserved in bacteria [6][7][8] . CarAB (spd_1132,spd_1131)encodes two subunits of carbamyl phosphate synthetase in Escherichia coli, and this enzyme catalyzes the formation of carbamyl phosphate, an intermediate in the pyrimidine nucleotide and arginine biosynthetic pathways 9 . It has been reported that carA mutation reduces the expression of capsule operon promoter (P cps ) in medium lacking uracil in the exponential growth period 7 , but it remains unclear whether several other genes affect the expression of P cps in S. pneumoniae.…”
Section: Introductionmentioning
confidence: 99%